Réquiem para un gentilhombre, an elegy against tradition - González Soto, Juan (2023)
The brief study shows how Manuel Scorza’s elegy, addressed to his friend Fernando Quíspez Asín, completely distances itself from the classical tradition. However, the elegy fulfills its mission: it shocks the reader, praises the deceased and makes the memory of his person remain in time.